Quantitative research on the training effect of youth basketball: impact on physical fitness indicators - a systematic review and meta-analysis - Liu, X.-D.; Li, Y.-T. (BMC Sports Science, Medicine and Rehabilitation, 2025)
This meta-analysis synthesizes evidence from 25 randomized controlled trials (N = 3,659) examining basketball training`s effects on adolescents` physical fitness parameters, revealing significant improvements in strength and explosive power with boys showing marked gains in standing long jump (effect size d = 0.71, 95% CI [0.34, 1.08], P = 0.0002) and pull-ups (d = 0.86, 95% CI [-0.02, 1.74], P = 0.05), while girls exhibited substantial increases in sit-up performance (d = 5.12, 95% CI [3.83, 6.40], P < 0.00001). Lung capacity also improved notably, particularly in boys (d = 0.39, 95% CI [0.16, 0.63], P = 0.001), though significant heterogeneity was observed across studies (I²=79-96%) due to variations in training protocols, baseline fitness levels, and measurement tools. Subgroup analyses demonstrated optimized outcomes with interventions exceeding 12 weeks and moderate training frequency (3-4 sessions weekly), providing evidence for designing structured basketball programs to enhance adolescents` physical development.